FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAYANAN WEBSITE BANK SYARIAH TERHADAP PEROLEHAN INFORMASI NASABAH (STUDI BNI SYARIAH KOTA BOGOR) - Nurma Yunita; Muhamad Komarudin; Andri Brawijaya (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2020)
This study aims to determine the most dominant factors affecting the quality of BNI syariah website services to obtain customer information in Bogor. The research method uses a questionnaire technique derived from 100 respondents of BNI Syariah customers in Bogor city. The results of this study indicate that navigation systems are accessibility, content, relevant, trust is the most dominant factor or the main factor to determine the quality of the services of the BNI Syariah website on obtaining customer information. Whereas website design factors up to date information transaction security, ease of communication are the supporting factors for the quality of BNI Syariah website services for customer information acquisition